Efeito da ingestão de bicarbonato de sódio na capacidade de sprints repetidos em jovens jogadores de futebol - Guimarães, Rodrigo dos Santos (2019)
Introduction: Ergogenic strategies have been studied to alleviate muscle fatigue and improve sports performance. Sodium bicarbonate (NaHCO3ˉ) has been shown to be effective for repeated sprint performance in adult team sports players, but the effect for adolescents is unknown. The aim of the present study was to evaluate the effect of NaHCO3ˉ supplementation on repeated sprint performance of young soccer players. Methods: Fifteen soccer players (15 ± 1 years; body fat 10.7 ± 1.3%) were recruited for this double-blind, placebo-controlled, crossover clinical study. The athletes ingested NaHCO3ˉ (0.3 g / kg) or placebo (0.2 g of sodium chloride / kg) 90 min before the repeated sprint protocol and repeated the same procedures after seven days of washout. Time to complete the sprint protocol and the vertical jump performance (CMJ), lactate, and the subjective perception of effort were evaluated. Results: NaHCO3ˉ supplementation promoted alkalosis (pH: 7.30 ± 0.01 vs 7.37 ± 0.01 and HCO3ˉ: 26.57 ± 0.31 vs 30.01 ± 0.35 mmol/L, p <0.001), but did not improve performance, power, CMJ, perception of fatigue or loss of muscle strength. Conclusion: Acute NaHCO3ˉ supplementation did not improve the performance of young soccer players undergoing a high intensity intermittent exercise protocol.